Pemanfaatan Jus Nanas sebagai Penurun Kolesterol dan Asam Urat pada Guru Madrasah Ibtidaiyah dan SMP Yayasan Ummul Quro Al-Hamidiyah - Ade Arinia Rasyad; Agnes Rendowaty; Nilda Lely; Masayu Azizah; Ema Ratna Sari; Erjon Erjon; Dewi Patmayuni; Lilik Pranata; Masayu Rosyidah (Institut Teknologi dan Bisnis Semarang, 2025)
Cholesterol and uric acid increase the risk of heart disease and stroke because they often occur together. To prevent and control cholesterol and uric acid, it is important to understand the causes, symptoms, and treatments. One way to reduce cholesterol and uric acid levels is pineapple juice, the purpose of the activity is to increase knowledge about the use of pineapple juice as a cholesterol and uric acid reducer in the community, the activity method with education and assistance in making pineapple juice, the activity was carried out on Elementary Madrasah and Junior High School Teachers, Ummul Quro Al-Hamidiyah Foundation, Jl. Kyai Muara Ogan Kertapati Palembang Mosque, totaling 15 people on December 19, 2024. The results of the activity stated that the teachers understood the function of pineapple and were able to practice in making juice. The conclusion of the activity stated that the teachers' knowledge increased after direct evaluation after education and assistance were carried out.